Can false memories prime alternative solutions to ambiguous problems?. Issue 1 (2nd January 2018) - Howe, Mark L.; Garner, Sarah R.
ABSTRACT: Research has demonstrated that false memories are capable of priming and facilitating insight-based problem-solving tasks by increasing solution rates and decreasing solution times. The present research extended this finding by investigating whether false memories could be used to bias ambiguous insight-based problem-solving tasks in a similar manner. Compound remote associate task (CRAT) problems with two possible correct answers, a dominant and a non-dominant solution, were created and normed (Experiment 1). In Experiment 2, participants were asked to solve these CRAT problems after they were given Deese/Roediger-McDermott lists whose critical lures were also the non-dominant solution to half of the corresponding CRATs. As predicted, when false memories served as primes, solution rates were higher and solution times were faster for non-dominant than dominant CRAT solutions. This biasing effect was only found when participants falsely recalled the critical lure, and was not found when participants did not falsely recall the critical lure, or when they were not primed. Results are discussed with regard to spreading activation models of solution competition in problem-solving tasks and current theories of false memory priming effects.